The effect of two-year application of pelargonic acid on the growth of Cirsium arvense (L.) Scop. and Sonchus arvensis L - Ganji, Eliyeh; Andert, Sabine (Frontiers in Agronomy, 2024)
Synthetic herbicides are used for perennial weed management, but owing to environmental and health concerns they face increasing regulatory restrictions. Consequently, there is growing interest in ecologically friendly alternatives including bio-herbicides based on natural compounds such as the active ingredient pelargonic acid (PA). PA acts as a broad-spectrum non-selective contact herbicide. However, when used as a contact herbicide, regrowth of the aboveground parts of plants still presents a challenge. The aim of this study was to investigate the control effect of a two-year application of PA on perennial weeds. The study was conducted between spring 2020 and autumn 2021 as a semi-field experiment. The factors were two levels of weed species (Cirsium arvense and Sonchus arvensis), three levels of herbicide treatment (untreated control, PA, and glyphosate), and three levels of initial ramet size (5, 10, and 15 cm). The results showed that a two-year application of PA increased its efficacy on C. arvense and S. arvensis when combined with the smaller initial ramet size (5 cm), but did not prevent regrowth in either species. PA efficacy was greater on C. arvense than on S. arvensis. The plant coverage decreased by 24 % when the initial ramet size was 5 cm for C. arvense, while for S. arvensis with the same initial ramet size it was reduced by just 4 %. For PA-treated C. arvense with an initial ramet size of 5 cm, aboveground biomass and belowground biomass were reduced by 43 % and 22 % respectively. In S. arvensis, the reductions in aboveground and belowground biomass for an initial ramet sizes of 5cm were 13 % and 12 % respectively. In general, PA efficacy was not as high as glyphosate efficacy for both species. In conclusion, the results revealed that after PA application the regrowth of shoots from the creeping roots in C. arvensis and S. arvensis decreased when the initial ramet size was 5cm. This reduction suggests that PA efficacy on these plants increases when it is applied repeatedly on the same patches with smaller initial root fragments.